Endek to be an International Clothes of G20 Summit - Ida Ayu Putu Widya Indah Sari (Bali Tourism Board, 2022)
Endek, as one of the Balinese woven cloths, has existed since the reign of King Dalem Waturenggong in Gelgel, Klungkung Regency. Since the 16th century, people in Bali have made their traditional cloth using hand-operated machine looms and other simple tools. The name Endek derives from gendekan or ngendek, which means silent or unchanged in color. Economic recovery efforts are a priority for the Province of Bali during the COVID-19 pandemic. Including increasing the value of Balinese cultural heritage, Endek woven fabrics. The government carries out massive promotions through various activities, exhibitions, to the promotion of Endek fabrics by international designer Christian Dior at Paris fashion week in 2020. In addition to having aesthetic value, Endek woven fabrics have high economic value for improving the welfare of weavers to SMEs. In the G20 Summit event in the province of Bali, the government proposed that state delegates attending the G20 Summit (KTT) wear clothes made from Endek or traditional Balinese woven fabrics. Later, the Balinese people would also get the opportunity to achieve a great economic benefit from the international event.